2020
DOI: 10.3390/jcm9113550
|View full text |Cite
|
Sign up to set email alerts
|

Hope in Advanced Cancer Patients in the Terminal Phase of Neoplastic Disease and Stability of Basic Mood

Abstract: The aim of this research is to compare the hope experienced by advanced cancer patients in the terminal phase of neoplastic disease in relation to the stability of their basic mood. The study group consisted of 246 patients, average age 59.5. The youngest respondent was 18 and the oldest was 90. The diagnostic tools used in the work comprised the Personal Card designed by T. Witkowski (PC) and an NCN-36 test (Block’s Hope test), designed by B.L. Block to measure the strength of hope in people struggling with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
1
10
1
2
Order By: Relevance
“…In our study, the difference between mean score of hope level and gender, age, marital status, educational status and employment was not statistically significant. In literature, although women are reported to be more disadvantaged than males in situations, such as mood disorders, depression and self-annihilation (19), there are also studies indicating no gender difference in terms of hope (16)(17). Our findings are consistent with the literature (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the difference between mean score of hope level and gender, age, marital status, educational status and employment was not statistically significant. In literature, although women are reported to be more disadvantaged than males in situations, such as mood disorders, depression and self-annihilation (19), there are also studies indicating no gender difference in terms of hope (16)(17). Our findings are consistent with the literature (20).…”
Section: Discussionsupporting
confidence: 92%
“…The study was carried out with the permission of İzmir Katip Çelebi (19) written consent (11). Patients who met the study criteria were informed about the study and informed consents were obtained from all volunteers.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…In a semi-experimental study with patients who experienced cancer recurrence for the first time, Herth 50 revealed a significant increase in the hope levels of patients who underwent the hope instilla- schizophrenia and that it is associated with many psychosocial variables. 24,50,51 For this reason, it is thought that the findings obtained from the study will guide nurses on hope instillation practices and make important contributions to the literature.…”
Section: Resultsmentioning
confidence: 99%
“…22 When the literature is analyzed, it is observed that the concept of hope is generally addressed in cancer disease. 23,24 In schizophrenia disorder, there are quite a limited number of studies in which hope is addressed, and it is observed that descriptive research designs are used in a significant part of these studies. 6,8,25 On the other hand, experimental studies on hope instillation in patients with schizophrenia could not be found.…”
mentioning
confidence: 99%
“…In the present study, we followed the methods of Baczewska et al, 2019a, Baczewska et al 2019b, Baczewska et al, 2020a, and Baczewska et al, 2020b [ 25 , 26 , 27 , 28 ]. It involved 246 participants at the terminal phase of the neoplastic disease.…”
Section: Methodsmentioning
confidence: 99%